Colovesical fistula as a complication of colonic diverticulosis: diagnosis with virtual colonoscopy - Işılay NADİR and Yasemin ÖZİN and Zeki Mesut Yalın KILIÇ and Dilek OĞUZ and Aysel ÜLKER and Kemal ARDA (Turkish Journal of Gastroenterology, 2019)
-